Template cohesion in perfume advertisements - Karpova , Kateryna; Popivniak, Olena; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article deals with features of perfume advertisements, in particular, cooperation of verbal and visual semiotic modes. It has been found that this cooperation is reflected in multimodal cohesion which is realized as reiteration of some mode components and sub-components in the set of perfume advertisements chosen for semiotic research. Reiteration of visual mode components is the background for selecting advertisements chosen according to the template cohesion. The whole multimodal cohesion investigation rests on template reiteration of verbal and corresponding visual components. For more detailed and thorough research the perfume advertisements of two different types have been chosen. The first type which has been distinguished as professional trader’s catalogue advertisement functions as a detailed verbal representation of perfume information, goods description. It represents verbal semiotic mode involving all mode components and a net of sub-components. The second type has been recognized as potential consumer’s advertisement. It has stressed on the visual semiotic mode representing detailed visualization of perfumery goods advertised giving some visual information which is not relevant to the perfume mentioned and described in the verbal semiotic mode. The whole research rests on template cohesion which belongs to the cross-advertisement cohesion, reiteration of visual semiotic mode components in the set of advertisements. Correlation of verbal and visual semiotic mode component and sub-component reiteration has helped to distinguish cryptic cohesion which has the intermediate position between verbal and visual semiotic modes, being a semi-independent element, it belongs simultaneously to both (verbal and visual) modes and it is very problematic to distinguish its definite belonging and connection with a definite mode. Revealing the cohesion is a very uncertain, hidden procedure. Verbal visualization creates cryptic cohesion which rests on typeface. According to the class of design typeface is divided into basic and additional. All classes are separated into eight cases of design devices. Further division is represented in twenty variations, which reflect typography codification as a set of typeface parameters. Cryptic cohesion has provided additional consolidation of perfume advertisements, grasping together verbal and visual semiotic modes, twisting these modes firmly in the chain of advertisements.